Relational Model between Parental Dental Belief and Formation of Dental Fear among Preschool Children in Indonesia - Setiawan, Arlette Suzy; Kendhawati, Lenny; Agustiani, Hendriati (European Journal of Dentistry, 2019)
Objective Parents’ behavior and belief can strongly impact preschool children. Parents play an important role in the formation of dental fear. The aim of the research is to analyze parental dental belief model as a source of dental fear among preschool children.Materials and Methods The research was undertaken at 15 kindergartens in Bandung City, Indonesia, which were chosen by means of multistage cluster random sampling. The participants of the research were parents and children aged 3 to 6. The research involved analysis of quantitative data to assess the relational model between parental dental belief and the formation of dental fear among children. While parental dental belief was measured using the Dental Belief Scale, children’s dental fear was measured using the Indonesian transadaptation of the Children’s Fear Survey Schedule-Dental Subscale based on parents’ report. The results were analyzed statistically by using structural equation modeling which is a combination of regression and factor analysis.Results The results indicate that the direct effect structural model of parental dental belief significantly fit the formation of dental fear among children in Bandung (t-value = 2.41).Conclusion The research concludes that parents’ perception and behavior—the latter contributing more—correlate with the formation of dental fear among preschool children.
Keywords: children; dental belief; dental fear; parents